Flood frequency analysis of annual maximum stream flows for Kuantan River Basin - Abdullah Mukmin, Ahmad; Noor Suraya, Romali; Sumiliana, Sulong (AIP Publishing, 2023)
Precise stream flow forecasting is essential in water management. Effective usage of flow estimates gives considerable assistance to water resources planning. In this study, five common distribution models, namely Generalized Extreme Value (GEV), Generalized Pareto (GP), Log-Pearson 3, Weibull (3P), and Log-normal were employed to identify the most appropriate probability distribution and to forecast the streamflows for the Kuantan River Basin. Yearly peak flow data from the Bukit Kenau station from 1977 to 2013 was used in the study. The best-fitted distribution model was evaluated using the Kolmogorov-Smirnov (K-S) goodness-of-fit test (GOF). The results show that Generalized Extreme Value (GEV) is the best-fitted flood distribution model, with a P-value of 0.997, followed by the Generalized Pareto, Log Pearson (3), Weibull, and Log-normal. The estimated peak flow values for 5, 10, 25, 50, 100, 200, 500 and 1000-year ARIs were 1569 m3/s, 1984 m3/s, 2560 m3/s, 3030 m3/s, 3535 m3/s, 4080 m3/s, 4868 m3/s, and 5521 m3/s respectively. The results of the peak flow for different ARIs might benefit future flood models and risk assessments conducted in this area of study.